Does education strengthen the life skills of adolescents? - Stefanie Schurer (IZA World of Labor, 2017)
Life skills, sometimes referred to as noncognitive skills or personality traits (e.g. conscientiousness or locus of control—the belief to influence events and their outcomes), affect labor market productivity. Policy makers and academics are thus exploring whether such skills should be taught at the high school or college level. A small portfolio of recent studies shows encouraging evidence that education could strengthen life skills in adolescence. However, as no uniform approach exists on which life skills are most important and how to best measure them, many important questions must be answered before life skill development can become an integral part of school curricula.
Keywords: J24; I26; P36; P46; 330; human capital development; life skills; noncognitive skills; secondary and tertiary education; measurement error